The Role of Traffic Police in Law Enforcement Against Traffic Violations as an Evaluation of Effectiveness in the Buol Police Area - Syarianti S. Kaco; Lucyane Djaafar; Nopiana Mozin (SEAN Institute, 2026)
Traffic is an important aspect of people's lives related to daily mobility, but the increasing level of violations indicates low compliance with the law, especially in Buol Regency. This study aims to analyze the role of the Buol Police Traffic Unit in enforcing the law against traffic violations and identify the factors that influence it. The method used is empirical legal research with a qualitative approach through observation, interviews, and documentation techniques. The results of the study indicate that the Buol Police Traffic Unit has implemented law enforcement through three main approaches, namely preventive, repressive, and curative, but its effectiveness has not been optimal. This is caused by various obstacles, such as low public legal awareness, lack of consistency and firmness of officers, and low levels of public trust. In addition, traffic violations are influenced by internal factors such as low discipline and knowledge of road users, as well as external factors such as infrastructure conditions, weak supervision, suboptimal administrative services, and a permissive community culture. In conclusion, traffic law enforcement in the Buol Police area needs to be carried out in a more comprehensive, consistent, educational, and sustainable manner to be able to increase public compliance and realize optimal traffic order and safety.